IDENTIFICACIÓN DEL FUSOBACTERIUM NUCLEATUM EN AGUDIZACIONES PERIAPICALES DURANTE LA TERAPIA DE CONDUCTOS - Chávez de Paz Villanueva, Luis Eduardo (2000)
The present study was performed to observe the extent to which Fusobacterium nucleatum remains in root canals of teeth present with interappointment endodontic flare-ups. Root canal samples from 30 patients suffering interappointment endodontic flare-ups were included in the study. The most frequent groups were: a) women from 36 to 45 years, b) mandibular premolars, c) long term carious processes and d) retreatments. Enucleatuin was identified in 10 samples that presented severe pain, exudate and swelling. These findings suggest the relation between the presence, of this microorganism and the production of the most severe symptoms; also remarks its capacity of survival in the root canal system after the cleaning procedures.